An Overview of Hepatitis B Virus Surface Antigen Secretion Inhibitors - Mohebbi, Alireza; Lorestani, Nazanin; Tahamtan, Alireza; Kargar, Niki L.; Tabarraei, Alijan (Frontiers in Microbiology, 2018)
Current anti-hepatitis B virus (HBV) regimen do not meet ideal result due to emerging resistance strains, cytotoxicity, and unfavorable adverse effects. In chronic HBV infection, high rates of sub-viral particles (SVPs) bearing HBV surface antigen (HBsAg) is a major obstacle regarding to raise effective immune responses and subsequently virus clearance. Development of potent HBsAg secretion inhibitors would provide a better insight into HBV immunopathogenesis and therapy. Investigating new non-toxic HBsAg secretion inhibitors targeting either viral or cellular factors could restore the immune response to remove virally infected hepatocytes after inhibiting SVPs. In this study, we overview several classes of HBV inhibitors with focus on their limitations and advantages over anti-HBsAg secretion potential.